Influences of alternate partial root-zone irrigation and urea rate on water- and nitrogen-use efficiencies in tomato - Xiaogang, Liu; Fusheng, Li; Fucang, Zhang; Huanjie, Cai; Qiliang, Yang (International Journal of Agricultural and Biological Engineering, 2017)
Traditional water and fertilizer inputs are often much higher than the actual demands of tomato, which causes a reduction in water- and fertilizer-use efficiencies. To investigate the advantage of alternate partial root-zone irrigation (AI) on water- and nitrogen (N)-use efficiencies of tomato modified by water and N management, taking conventional irrigation (CI) as the control, the effects of AI on root morphology and activity, fruit yield and water and N use efficiency were studied using pot experiments. There were four combinations of irrigation levels and growing stages of tomato for AI, i.e. AI1 (high water (WH) from blooming to harvest stage (BHS)), AI2 (WH from blooming to fruit setting stage (BFS) and low water (WL) at the harvest stage (HS)), AI3 (WL at BFS and WH at HS) and AI4 (WL at BHS) at three urea rates, i.e. low urea rate (NL), middle urea rate (NM) and high urea rate (NH) in the form of urea. Irrigation quotas for WH and WL in AI at BFS or HS were 80% and 60% of that in CI, respectively. Compared to CI, AI decreased water consumption by 16.0%-33.1% and increased water use efficiency of yield (WUEy) and dry mass (WUEd) by 6.7%-11.9% and 10.2%-15.9%, respectively. AI1 did not decline yield, total N uptake (TNU) and N use efficiency (NUE) significantly. Compared to NL, NM enhanced tomato yield, TNU, WUEy and WUEd by 28.5%, 35.3%, 22.6% and 16.3%, respectively. Compared to CINL, AI1NM reduced water consumption by 12.5%, but increased tomato yield, TNU, WUEy and WUEd by 35.5%, 58.4%, 54.4% and 53.7%, respectively. Therefore, AI1 can improve water use efficiency and total N uptake of tomato simultaneously at medium urea rate.Keywords: alternate partial root-zone irrigation, nitrogen level, nitrogen uptake, tomato, water use efficiency, yieldDOI: 10.25165/j.ijabe.20171006.2541Citation: Liu X G, Li F S, Zhang F C, Cai H J, Yang Q L. Influences of alternate partial root-zone irrigation and urea rates on water- and nitrogen-use efficiencies in tomato. Int J Agric & Biol Eng, 2017; 10(6): 94–102.